OUTSTANDING MADRASAH WITH BILINGUAL CLASS - Farida Hanun (Jurnal Dialog, 2018)
English This qualitative study on Outstanding Madrasah with bilingual classes is aimed to reveal how the implementation of Bilingual class programs is conducted at State Primary Madrasah (MIN) I South Tangerang City. The findings indicate that: (a) the implementation of bilingual class program is projected to prepare the generation with foreign language profeciency, (b) bilingual program is supported by collaboration with Cambridge International Institute, the roles of madrasah committee and the support of madrasah headmaster in the quality of education, (c) the inhibiting problem of bilingual class with cooperative model is time consuming and sufficient infrastructure and learning resources, (d) Ministry of Religious Affairs should pay attention to the madrasah facilities that apply a bilingual class program for a better learning process. Indonesia Penelitian Madrasah Berprestasi dengan kelas bilingual bertujuan mengetahui pelaksanaan program kelas Bilingual di MIN I Kota Tangerang Selatan dengan metode kualitatif. Hasil penelitian menunjukkan bahwa: (a) penyelenggaraan program kelas bilingual menghasilkan generasi penerus yang berkualitas dan menguasai bahasa asing, (b) faktor pendukung program bilingual adalah adanya jaringan kerjasama dengan Lembaga Cambride International, peranan komite madrasah dan dukungan kepala madrasah terhadap peningkatan kualitas pendidikan, (c) faktor penghambatnya yakni pembelajaran bilingual dengan model kooperatif membutuhkan waktu yang lebih banyak, belum lengkap sarana prasarana dan sumber belajar, (d) Kementerian Agama harus memperhatikan kebutuhan sarana prasarana madrasah penyelenggara program kelas bilingual sehingga dapat menunjang pembelajaran menjadi lebih baik.